2017
DOI: 10.1111/iwj.12717
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of clinically relevant wound bacteria using autofluorescence image‐guided sampling in diabetic foot ulcers

Abstract: Clinical wound assessment involves microbiological swabbing of wounds to identify and quantify bacterial species, and to determine microbial susceptibility to antibiotics. The Levine swabbing technique may be suboptimal because it samples only the wound bed, missing other diagnostically relevant areas of the wound, which may contain clinically significant bacteria. Thus, there is a clinical need to improve the reliability of microbiological wound sampling. To address this, a handheld portable autofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
0
40
0
3
Order By: Relevance
“…As infection differs from contamination in that it represents invasion of the host tissues, samples for culture of tissues are likely to provide more accurate data than superficial swabs. In the study by Ottolino‐Perry et al, real‐time autofluorescence was found to be useful for both assessing the “wound bioburden” and improving the sensitivity of swab cultures . In addition to the fact that current guidelines recommend against using swabs to collect wound specimens for microbiological assessments and the results of the recent Concordance in Diabetic Foot Ulcer Infection (CODIFI) study demonstrate the greater accuracy of tissue compared with swab specimens, the findings of the Ottolino‐Perry et al's study are mitigated by the fact that there is no widely accepted or validated definition of “wound bioburden.” The detection of pathogenic virulence genes is an interesting avenue of research that may help differentiate colonizers from pathogens, but studies to date have only included monomicrobial Staphylococcus aureus DFIs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As infection differs from contamination in that it represents invasion of the host tissues, samples for culture of tissues are likely to provide more accurate data than superficial swabs. In the study by Ottolino‐Perry et al, real‐time autofluorescence was found to be useful for both assessing the “wound bioburden” and improving the sensitivity of swab cultures . In addition to the fact that current guidelines recommend against using swabs to collect wound specimens for microbiological assessments and the results of the recent Concordance in Diabetic Foot Ulcer Infection (CODIFI) study demonstrate the greater accuracy of tissue compared with swab specimens, the findings of the Ottolino‐Perry et al's study are mitigated by the fact that there is no widely accepted or validated definition of “wound bioburden.” The detection of pathogenic virulence genes is an interesting avenue of research that may help differentiate colonizers from pathogens, but studies to date have only included monomicrobial Staphylococcus aureus DFIs .…”
Section: Discussionmentioning
confidence: 99%
“…Ottolino-Perry et al, 64 real-time autofluorescence was found to be useful for both assessing the "wound bioburden" and improving the sensitivity of swab cultures. 64 In addition to the fact that current guidelines recommend against using swabs to collect wound specimens for microbiological assessments 8,9 The suspicion of osteomyelitis complicating an infected DFU is based on assessing clinical findings (eg, deep ulcer over a bony prominence, visible exposed bone, positive PTB test, and "sausage toe" appearance), laboratory tests (eg, serum biomarkers, tissue histology, and microbiology), and imaging studies (eg, cortical disruption, sequestrum, involucrum, marrow oedema, or tracer uptake) for bone abnormalities. 8,9 In one study, the combination of two relatively simple, widely available, and inexpensive tests-the PTB test and plain Xrays-was quite accurate with a reported sensitivity/specificity of 97%/93% in a population of high-risk patients and provided better results for diagnosing osteomyelitis than when the tests were considered separately.…”
Section: 4mentioning
confidence: 99%
“…Durch die Methodik der Autofluoreszenz konnte vergleichsweise akkurater das Vorhandensein von bakterieller Besiedlung definiert werden [22]. Durch die AF-Darstellung könnte frühzeitig die Indikation zur operativen Therapie gestellt werden.…”
Section: Diskussionunclassified
“…Ein gezieltes, frühes Débridement und eine gezielte Wundreinigung sind dadurch möglich [20]. [22]. Eine grüne Fluoreszenz wird bei Erregern wie Pseudomonas aeruginosa (PA), durch eine Emission von 405 nm hervorgerufen.…”
Section: Introductionunclassified
“…Technologies that supplement clinician judgement, particularly from a microbial load perspective, will aid more targeted approach to wound infection. New guidance devices such as Moleculight i:X ™, (Moleculight Inc., Toronto, Canada), which not only measure wound surface area but can also detect fluorescent bacteria above a threshold (>10 4 cfu/g), may aid more targeted sampling and support informed treatment decisions . Moreover, this is an important bridge to drive infection diagnostics, highlighted by the UK AMR strategy and the O'Neill report as one of the key focus areas to tackle AMR.…”
Section: How Can Dressings Containing Ncs Be Incorporated Into Clinicmentioning
confidence: 99%